CLONING, EXPRESSION AND LYTIC EFFICACY ASSESSMENT OF THE STAPHYLOCOCCUS AUREUS PHAGE LYSIN GENE - Thuy Duong, Bui Thi; Duy, Nguyen Dinh; Khang, Dinh Duy; Thuan, Nguyen Huy; Minh Huong, Nguyen Thi; Quyen, Dong Van (Vietnam Journal of Biotechnology, 2018)
The discovery of antibiotics is considered to be one of the greatest medical achievements in the early part of 20th. Over the past six decades, these ‘wonder drugs’ have played a critical role in reducing the global burden of communicable diseases. As a country in the tropical zone, Vietnam faces numerous infectious disease outbreaks every year. In addition, the overuse of antibiotics in healthcare and the misuse of antibiotics as growth promoter in agriculture these past decades have led to serious antibiotic-resistance in bacterial pathogens of human, crops and livestock in Vietnam. This poses an urgent need for alternative strategies to fight against these pathogens. Lysins are phage-encoded peptidoglycan hydrolases which were recently demonstrated the strong potential in human and veterinary medicine to control and treat pathogens on mucosal surfaces and in systemic infections. These enzymes when applied exogenously to Gram-positive bacteria, bring about rapid lysis and death of the bacterial cell and therefore promise an effective alternative therapy against antibiotic-resistant bacterial pathogens. In this study, we applied the DNA technology to produce a recombinant S. aureus lysin (LysK). LysK was PCR amplified from phage S. aureus and cloned into a pET32a(+) expression vector. The recombinant fusion protein (LysK-Trx) was successfully expressed in E. coli, purified through nickel column chromatography, and further digested with Thrombin protease. The cleaved protein (intact LysK) was purified by nickel column again. The recombinant LysK was tested for its ability to kill S. aureus by a spot inoculation assay. The results showed that recombinant LysK induced the lysis of host bacteria, indicating that the protein was expressed and functionally active. Data from the current study can be used to develop therapeutic tools for treating diseases caused by drug-resistant S. aureus strains in Vietnam.